A Review on Herbal Drug Interaction - Chhabra, Anshu; Singh, Gurvinder; Upadhyay, Yash (Asian Journal of Pharmaceutical Research and Development, 2020)
Herbal medicines are becoming popular worldwide, despite their mechanisms of action being generally unknown, the lack of evidence of efficacy, and inadequate toxicological data. An estimated one third of adults in developed nations and more than 80% of the population in many developing countries use herbal medicines in the hope of promoting health and to manage common maladies such as colds, inflammation, heart disease, diabetes and central nervous system diseases. To date, there are more than 11 000 species of herbal plants that are in use medicinally and, of these, about 500 species are commonly used in Asian and other countries. These herbs are often co-administered with therapeutic drugs raising the potential of drug–herb interactions, which may have important clinical significance based on an increasing number of clinical reports of such interactions.The interaction of drugs with herbal medicines is a significant safety concern, especially for drugs with narrow therapeutic indices (e.g. warfarin and digoxin). Because the pharmacokinetics and/or pharmacodynamics of the drug may be altered by combination with herbal remedies, potentially severe and perhaps even life-threatening adverse reactions may occur. Because of the clinical significance of drug interactions with herbs, it is important to identify drugs and compounds in development that may interact with herbal medicines. Timely identification of such drugs using proper in vitro and in vivo approaches may have important implications for drug development.